Occupational lifting and risk of hypertension, stratified by use of anti-hypertensives and age - a cross-sectional and prospective cohort study - Korshøj, Mette (BMC Public Health, 2021)
BACKGROUND: Heavy occupational lifting is prevalent in the general working population and is sparsely reported to associate with hypertension, especially among older and hypertensive workers. We investigated if heavy occupational lifting is associated with hypertension and blood pressure (BP) in both cross-sectional and prospective study designs in the Copenhagen General Population Study, stratified by age, and use of anti-hypertensives. METHODS: Participation was conducted following the declaration of Helsinki and approved by the ethical committee (H-KF-01-144/01). By multivariable logistic and linear regression models, we investigated the association between heavy occupational lifting and hypertension, in a cross-sectional design (n = 67,363), using anti-hypertensives or BP ≥140/≥90 mmHg as outcome, and in a prospective design (n = 7020) with an above-median change in systolic BP (SBP) from baseline to follow-up and/or a shift from no use to use of anti-hypertensives as outcome, with and without stratification by age and use of anti-hypertensives. RESULTS: The odds ratio for hypertension was estimated at 0.97 (99% CI: 0.93–1.00) in the cross-sectional analysis, and at 1.08 (99% CI: 0.98–1.19) in the prospective analysis. The difference in SBP among workers with versus without heavy occupational lifting was estimated at − 0.29 mmHg (99% CI -0.82 – 0.25) in the cross-sectional and at 1.02 mmHg (99% CI -0.41 – 2.45) in the prospective analysis. No significant interaction between heavy occupational lifting and age, nor use of anti-hypertensives were shown. CONCLUSIONS: Only the prospective analysis indicated heavy occupational lifting to increase the risk of hypertension. Further research on the association between occupational lifting and hypertension are needed. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12889-021-10651-w.